Expression of apelin is related to oxidative damage in heart tissue of rats during chronic systemic hypoxia - H R Helmi; Frans Ferdinal; Ani Retno Prijanti; Sri Widia A Jusman; Frans D Suyatna (Acta Biochimica Indonesiana, 2018)
Background: Chronic systemic hypoxia is severe environmental stress for the heart and might lead to the development of heart failure. Apelin is an endogenous peptide that has been shown to have various beneficial effects on cardiac function. Apelin appears to have a role to play in the ventricular dysfunction and maintaining the performance of the heart. Objectives: In the present study we want to investigate the adaptive response of heart tissue to chronic systemic hypoxia and the correlation with apelin expression and oxidative stress in rat. Methods: An experimental study was performed using 28 Sprague-Dawley male rats, 8 weeks of age. Rats were divided into 7 groups 4 each, namely control group; normoxia (O2 atmosphere) and the treatment group of hypoxia (8% O2) for 6 hours; 1;3;5;7 and 14 days respectively. Body weight and heart weight were measured at each treatment. Ventricular thickness was measured by caliper, Apelin mRNA was measured using real-time qRT-PCR with Livak formula and malondialdehyde (MDA) level was used to assess oxidative stress due to cardiac tissue hypoxia. Results: Macroscopic exams showed hypertrophy at day 7th. The relative expression of Apelin mRNA in hypoxic heart is decreased at the beginning and then increased, starting from day-7 to day-14. The MDA levels were significantly increased from day-7 and were strongly correlated with relative expression Apelin. Conclusion: It is concluded that the increase of Apelin expression is related to oxidative stress in heart tissue of rats during chronic systemic hypoxia.